ChemInform Abstract: Facile Preparation of Highly‐Functionalized, Nitrogen‐Bearing Diarylmethanes. Issue 15 (25th March 2013) - Schmink, Jason R.; Tudge, Matthew T.
Abstract A novel Pd‐catalyst is employed for the Suzuki coupling of heterocyclic chloromethyl derivatives with arylboronic acids under mild conditions.